SOME DEFINITE INTEGRALS OF GRADSHTEYN-RYZHIK AND OTHER INTEGRALS (Global Journal of Science Frontier Research, 2011)
In the present paper we evaluate three definite integrals with certain convergence conditions, using Leibnitz rule for differentiation under integral sign and Wallis formula. Some other integrals are also evaluated by means of Leibnitz rule, Kummer's first transformation and reduction formula, series rearrangement techniques under stated convergence conditions.
Keywords: Leibnitz rule for differentiation under the integral sign; Generalized Gaussian Hypergeometric Function; Kamp´e de F´eriet’s General Double Hyperg